Exploring the interplay of mental health knowledge, stigma, and social distance among clinical nurses: a study in Liaoning, China - Wang, Weiwei; Xia, Junhong; Chen, Wei; Ye, Junhua; Xie, Kun; Zhang, Zhuona; Binti Mohamad, Siti Mardhiana; Shuid, Ahmad Naqib (Frontiers in Psychiatry, 2025)
BackgroundStigma related to mental health conditions has a negative impact on both the nursing staff and their patients. Most of the current research on stigma explores the impact of single factors on stigma and does not explore the relationship between knowledge, social distance and stigma among clinical nurses.MethodsA convenience sampling method was used to conduct a questionnaire survey among 628 nurses from five hospitals in Liaoning Province in March 2021 and June 2021 using a combination of online and offline methods. To study the negative attitudes toward patients with mental illness among clinical nurses and to analyze the relationship between mental ill health stigma, social distancing, and mental health knowledge among nurses. The questionnaire includes Sociodemographic data, Scale for Assessing the Stigma of Mental Illness in Nursing (score range: 20 100, the higher the score, the less stigma attached to mental ill health), Mental Illness Social Distance Scale (score range: 6 30, the higher the score, the greater the social distance) and Mental Health and Mental Health Knowledge Questionnaire (score range: 0 25, the higher the score, the higher the knowledge level).ResultsThe nurses’ mental ill health stigma score was 58.96 ± 9.38 points, the mean scores of psychiatric and general nurses were 58.86 ± 9.33 and 59.41 ± 9.58 points, respectively. Willingness to become a psychiatric nurse is a factor influencing the stigma of mental illness. The stigma of mental ill health, social distance and mental health knowledge of nurses are positively correlated (P<0.01). The mediation analysis demonstrated that mental health stigma significantly mediated the relationship between mental health knowledge and social distance (a= 0.599, P<0.001; b= -0.194, P<0.001). After accounting for stigma, the direct effect of mental health knowledge on social distance was no longer significant (c’=-0.007, P=0.078), highlighting the central role of stigma in this relationship.ConclusionsNurses mental ill health stigma is moderate and is the main mediating effect between mental health knowledge and social distancing. The pivotal role of mental health knowledge in shaping nurses’ attitudes and behaviors pertaining to social distancing in the context of mental illness. By combating stigma and enhancing mental health literacy among healthcare practitioners, we can foster environments that promote inclusive and compassionate care practices, thereby ameliorating patient outcomes and redressing disparities in mental health treatment.